Studies On Metallo-fJ-Lactamse Producing Pseudomonas Aeruginosa And Acinetobacter In A Tertiary Care Hospital And Development Of A Simple Screening Test For Its Detection - Ng Woei, Kean (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
The clinical utility of carbapenems is under threat with the emergence of acquired carbapenemases producing bacteria, particularly metallo-~-lactamases (MBLs). Such enzymes have emerged in bacteria in many geographical locations and often confer highlevel of resistance to all ~lactams antibiotics except aztreonam. The prevalence of MBLs have been studied in many countries but not been done yet in Malaysia. Besides, rapid detection of MBLs-producing Gram-negative bacilli is critical to prevent their widespread dissemination. Thus far, no standardized detection method is available for routine laboratory used. The purpose of the study is to detennine the isolation rate of MBLsproducing P. aeruginosa, Acinetobacer baumannii and Acinetobacter spp in clinical samples from Hospital Universiti Sains Malaysia (HUSM) within year 2007 and also to develop a chelating agent based double disk synergic test and disk potentiation test for detection of MBL-producing P. aeruginosa and Acinetobacter isolated from clinical samples. During year 2003-2007, the resistance of P. aeruginosa to imipenem (carbapenem group's antibiotic) ranged between 11-20 % while for Acinetobacter spp it was 44-71 %. Out of the 22 strains of carbapenem resistant P. aeruginosa, 17 (77 .3 %) were positive for MBLs. However, only 3.5 % Acinetobacter spp was positive for MBLs. None of the Acinetobacter baumannii was positive for MBL. The disk potentiation test with 2-mercaptopropionic acid (2-MP A) in dilution of 1: 12 provided more conclusive and accurate result in detecting MBL-producing strains. In disk potentiation test, the diameter of enlargement of growth inhibitory zone by 5 mm or more (cutoff value) around CAZ + 2- MP A disk compared to CAZ disk has accurately detected MBL-producing strains. The sensitivity and specificity of the test was 89.5% and 100% respectively for P. aeruginosa and I 00 % sensitivity and specificity for Acinetobacter. This study is the first report of high prevalence of MBL-producing P. aeruginosa in a tertiary care hospital in Malaysia. The study also reports the validation of a simple and accurate MBL detection method that can be easily incorporated into the routine clinical laboratory.